Food and Nutritional Security Status: Assessment among Landless People in Chitwan, Nepal - Poudel, Dikshit; Dhungana, Suryamani; Tripathi, Kalyani Mishra; Kaphle, Krishna; Sah, Shrawan Kumar (International Journal of Applied Sciences and Biotechnology, 2018)
Food insecurity, sadly still remains a concern with Nepal. The remote settlement of communities, harsh terrains, inequity in income generation have left millions of Nepalese experiencing some level of food insecurity mostly among marginalized population in both urban and rural settings. A pilot study was conducted within ninety households of four different locations with the purpose to assess various dimensions of food and nutritional security of the landless people living in undocumented land by purposive selection of Chitwan District of Nepal. Semi-structured questionnaire was used to obtain primary data and secondary data was obtained from Bharatpur Municipality and Madi Agriculture Service Centre, Chitwan. Analysis revealed 57.77% household expressed themselves as food secured in terms of their production and source of income while 42.23% were food insecure. The most food insecure ethnic group was Janajatis (indigenous) (34.21%) followed by Dalits and Brahmins (15.78%). Similarly, 79.99% (36.66% male, 43.33% female) respondents were under-nutrition and 20.01% (5.56% male and 14.45% female) were nutritionally secured from calculation using Harris-Benedict principle based on net calories they obtained from their daily meal. Females were more insecure in terms of population size, education, skill, nutrition and diseases followed by males. Of those interviewed, 57.77% households lack production activity and were also food insufficient. Main source of income was off-farm work (40%) followed by remittance (35.56%). Various natural calamities were also the reason behind being landless in case of some households and they reportedly migrated from elsewhere. Still, peoples are involved in foraging and traditional farming activities with low output. Addressing agricultural production, nutrition awareness, climate change monitoring, livelihoods strengthening and disaster preparedness to ensure access to food is urgent need even in urban areas like Chitwan. Dependence on food import, shying from production activities, traditional food sources has to be addressed for Nepal’s struggle against food insecurity. Int. J. Appl. Sci. Biotechnol. Vol 6(4): 351-358